Pengaruh Social Media Marketing, Education Service Quality terhadap Kepuasan Orang Tua Pada SDIT Bunayya Medan Sunggal melalui Brand Image sebagai Variabel Intervening - Rizki Nurafrilia Harahap; Fadli Fadli; Evawany Yunita Aritonang (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2026)
This study's overarching goal is to dissect how SDIT Bunayya Medan Sunggal's social media marketing and the quality of its educational services affect the school's reputation and the happiness of its parents. In order to take a quantitative approach, we gave parents surveys to fill out, and then we used route analysis to look for direct and indirect relationships between the factors. Brand Image and Parental Satisfaction are unaffected by Social Media Marketing, according to the results. On the other hand, Education Service Quality significantly and positively affects both of these factors. Although brand image did not mediate the impact of social media marketing, it did improve parents' satisfaction and mediate the influence of education service quality. Parents' impressions and satisfaction are largely determined by the quality of educational offerings, according to these studies. For a more complete picture, future studies should incorporate other factors like family trust or school communication.